Identifikasi Faktor-Faktor yang Mempengaruhi Sales performance pada Perusahaan Media Periklanan : Studi Empirik pada Tenaga Penjual di RCTI - Utomo, Endhar Priyo (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
This research was conducted because of the gap from the results of previous research (research gap) regarding the level of sales experience can affect sales performance and empirically examine the factors that influence sales performance such as salesperson skills, sales interaction quality and effectiveness of sales activities.The purpose of this study is to build a conceptual model to describe and provide answers to the gap between sales experience variables on sales performance, and empirically examine the factors that influence Sales performance. This study uses a population of all RCTI's marketing department workforce. This study uses the Judgment Sampling method of respondents which was determined as a study sample of 120 people. The analysis technique used in interpreting and analyzing research data is the Structural Equation Model (SEM) technique from the AMOS 20 software package. The results of hypothesis testing proved that the sales experience factor, salesperson skill, sales interaction quality and effectiveness of sales activities had a positive effect on significant sales performance. The research model can be accepted, from the results calculated by the suitability index where the chi-square value is 200,633, probability value 0.027, TLI value 0,974, CFI value 0,977, CMIN / DF 1,223 and RMSEA 0,043 all of which meet the requirements even though the GFI value is 0,880 and AGFI 0,846 can marginal accepted.